Root coverage with bridge flap - Pushpendra Kumar Verma; Ruchi Srivastava; T P Chaturvedi; Krishna Kumar Gupta (Wolters Kluwer Medknow Publications, 2013)
Gingival recession in anterior teeth is a common concern due to esthetic reasons or root sensitivity. Gingival recession, especially in multiple anterior teeth, is of huge concern due to esthetic reasons. Various mucogingival surgeries are available for root coverage. This case report presents a new bridge flap technique, which allows the dentist not only to cover the previously denuded root surfaces but also to increase the zone of attached gingiva at a single step. In this case, a coronally advanced flap along with vestibular deepening technique was used as root coverage procedure for the treatment of multiple recession-type defect. Here, vestibular deepening technique is used to increase the width of the attached gingiva. The predictability of this procedure results in an esthetically healthy periodontium, along with gain in keratinized tissue and good patient's acceptance.